Método para análise de medidas do uso racional da água no novo terminal de passageiros do aeroporto de Vitória-ES - Negreiros, Lícia Rodrigues (2014)
The international airports has been committed globally with the adoption and management of environmental sustainability practices, encouraged not only by the requirement contained in local laws, but also on the instructions of non-governmental organizations such as the United Nations (UN); by tax incentive policies; by positive results, proven and reported in case studies; and by instructions of international institutions dedicated to the certification of environmental sustainability in the built environment. In this way, this study sought to compile and present case studies relating to environmental sustainability actions taken at airports worldwide and present the main certifications of environmental sustainability for the built environment. After this overview, this work focused on research in the rational use of water, addressing the consumption of water issues in airports and identifying the environmental sustainability requirements, for that focus, recorded in the certification Leadership in Energy and Environmental Design (LEED) and Process AQUA-HQE - High Environmental Quality, in the database of the Sustainable Aviation Guidance Alliance (SAGA), and Memorial Sustainable Criteria for Enterprises (MCSE), prepared by Infraero as a basic guide for the development of sustainable projects of Brazilian airports under its management. To the identified requirements were relate actions, which were compared for the verification of similarities and common goals. This comparison gave a concise set of actions aiming the rational use of water resources, also by reducing the water consumption through the use of economizers sanitary equipment. This has enabled a suggestion to adapt the MCSE, by the incorporation of new actions, for example; as well as the application of some of these actions to sanitary uses at passenger terminal of Vitoria/ES Airport through the development and analysis of scenarios that have concluded the capability of sustainable actions in reducing the demand for water for sanitary purposes in passenger terminals of airports.